2009
DOI: 10.1080/08039480802294787
|View full text |Cite
|
Sign up to set email alerts
|

Substance use at admission to an acute psychiatric department

Abstract: Substance use is prevalent in patients with psychiatric disorders and may cause severe symptoms in addition to complicating the diagnosis of psychiatric disorders. The aims of the study were to find the prevalence in use of alcohol, drugs, benzodiazepines, hypnotics, opiates and stimulants, and to find the prevalence of substance use disorders at admission to an acute psychiatric department receiving all admissions from a catchment area. Patients were interviewed about use of medications and intoxicating subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 33 publications
5
36
1
2
Order By: Relevance
“…Our findings confirm the shortcomings of on-site urine testing in a clinical setting (30,191) and demonstrate the additional information obtained by comprehensive laboratory screening (90,191) (Table 9). …”
Section: On-site Urine Testing Identified Cannabis Use That Was Not Rsupporting
confidence: 84%
See 3 more Smart Citations
“…Our findings confirm the shortcomings of on-site urine testing in a clinical setting (30,191) and demonstrate the additional information obtained by comprehensive laboratory screening (90,191) (Table 9). …”
Section: On-site Urine Testing Identified Cannabis Use That Was Not Rsupporting
confidence: 84%
“…With this exception, the study was conducted in accordance with the declaration of Helsinki (167). Other recent studies have also been performed without informed consent of the patients (80,90), and some previous studies performed drug analyses under the guise of other somatic tests (143,148). We experienced in the main project that informed consent very well can be obtained, within a few days after admission, and we recommend future studies to do so.…”
Section: Ethical Considerationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with our findings, an Indian study conducted in a tertiary care center showed that alcohol-use disorders account for 29% of substance-use disorders 35 . In Norway, approximately onethird of the admissions in an acute psychiatric ward had a substanceuse disorder 36,37 . This discrepancy may be explained by the fact that patients with substance-use disorders in SA are, according to national policy, admitted to separate addiction facilities.…”
Section: Discussionmentioning
confidence: 99%